1981
DOI: 10.1111/1365-3040.ep11604553
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of rehydration of detached sunflower leaves from different initial water deficits

Abstract: The tempo of rehydration of sunflower (Helianlhus annuus L.) leaves was measured after dehydration in a pressure bomb down to water potentials of -0.5 to -1.6 MPa, When rehydrated f"rom small water deficits ( -0.5 to -0.8 MPa) the plot of log rehydration rate versus time is concave. When rehydration starts from large deficits (-1,2 to -1.6 MPa) the semilog plot has a characteristic shoulder, i.e. a rehydration phase of long half-time is followed by a phase of short half-time. The experimental curves were fitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…When an estimate of root fresh volume is derived from their dry mass, it is apparent that the total amount of water moved in the transient phase could be easily accounted for by changes in living tissue capacitance in our experiment. Nevertheless, we think that this was not the case: the kinetics of capacitive exchange are always considerably slower and the time constant greatly increases with tissue length and longitudinal resistance (Stroshine et al 1985;Tyree et al 1981). Similar results have been obtained by the cell pressureclamp technique.…”
Section: Discussionsupporting
confidence: 70%
“…When an estimate of root fresh volume is derived from their dry mass, it is apparent that the total amount of water moved in the transient phase could be easily accounted for by changes in living tissue capacitance in our experiment. Nevertheless, we think that this was not the case: the kinetics of capacitive exchange are always considerably slower and the time constant greatly increases with tissue length and longitudinal resistance (Stroshine et al 1985;Tyree et al 1981). Similar results have been obtained by the cell pressureclamp technique.…”
Section: Discussionsupporting
confidence: 70%
“…The most detailed study so far (Tyree et al, 1981) was not able to reach a firm conclusion. Things are simpler in a larger leaf with greater volumes of homogeneous tissue like Agave, where Smith & Nobel (1986) were able to decide in favour of a cell to cell path.…”
Section: Historical -Explorations Of Water Paths In Leavesmentioning
confidence: 89%
“…The developments have been ably reviewed by Boyer (1985), himself responsible for emphasising the complications arising from nonreversible entrapment of water in tissues that are growing. The models have become greatly elaborated 1981, Molz & Ferrier, 1982, but the following considerable simplification has been distilled out of the complexities.…”
Section: Historical -Explorations Of Water Paths In Leavesmentioning
confidence: 99%
“…Apoplastic tracer studies (Canny, 1986) and the discovery of aquaporins (Agre et al, 1993;Chrispeels and Agre 1994) have promoted the view in recent years that transmembrane flow may dominate outside-xylem transport (Tyree et al, 1981(Tyree et al, , 1999Sack and Tyree, 2005), at least in the light, when aquaporins may be activated (Cochard et al, 2007). However, a theoretical study by Buckley (2015) that used membrane permeability values from published studies carried out on illuminated leaves concluded that apoplastic transport should dominate.…”
Section: Does Liquid Flow Outside the Xylem Follow Apoplastic And/or mentioning
confidence: 99%